2018
DOI: 10.1007/s10903-018-0846-y
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Feasibility and Uptake of HPV Self-Sampling Among Immigrant Minority Women: a Focused Literature Review

Abstract: This review uncovers the extent to which immigrant and minority women find HPV self-sampling an acceptable and feasible alternative to PAP testing for screening for cervical cancer. A focused literature review was conducted using CINAHL, Medline, Proquest and Pubmed databases to search for content relating to acceptability or feasibility of HPV self-testing for immigrant populations or minorities. 575 prospective relevant papers were included in the final analysis and 28 selected using the inclusion and exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…There are often more similarities than differences between ethnic groups of immigrant women regarding participation in screening and they experience considerable stress associated with their minority status which in itself hinders participation 43‐45 . However, the findings in our study may mostly reflect the general view of ethnic minority women predominantly from the Middle East and Somalia in deprived areas in a health‐care system which is publicly funded and in other ways similar to Denmark in terms of number of immigrants, social inequalities, etc…”
Section: Discussionmentioning
confidence: 68%
“…There are often more similarities than differences between ethnic groups of immigrant women regarding participation in screening and they experience considerable stress associated with their minority status which in itself hinders participation 43‐45 . However, the findings in our study may mostly reflect the general view of ethnic minority women predominantly from the Middle East and Somalia in deprived areas in a health‐care system which is publicly funded and in other ways similar to Denmark in terms of number of immigrants, social inequalities, etc…”
Section: Discussionmentioning
confidence: 68%
“…A strategy suggested by the participants to help reduce barriers to CCS is offering the possibility of using self-sampling tests. This has been explored as a potentially good alternative to conventional CCS that can increase participation among migrants [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through cervical cancer screening (CCS), precancerous lesions are detected; treatment of these lesions can stop further progression to cervical cancer [ 4 ]. CCS involves the collection of cervical cells usually performed by a clinician during a gynecological examination at a health facility, but self-sampling has been explored as an alternative [ 4 , 5 ]. Evidence shows that CCS reduces morbidity and mortality [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research findings, including meta-analyses, have demonstrated that self-collected cervico-vaginal samples are at least as sensitive as provider-collected cervical samples for cytology or hrHPV testing when it comes to detecting potentially cancerous lesions (Arbyn, Smith, Temin, Sultana, & Castle, 2018;Arbyn et al, 2014;Racey et al, 2013;Snijders et al, 2013). Researchers also have found that a large majority of women find self-collection both acceptable and feasible (Marshall, Vahabi, & Lofters, 2019;Nelson et al, 2017;Racey et al, 2013). Currently in the United States, self-collection of samples for HPV testing is only approved for use in research settings; however, it is emerging as a way to improve equity in CCS if implemented in person-centered, culturally sensitive ways.…”
mentioning
confidence: 99%
“…The aim of this review was to critique research design and results of studies assessing self-collection of samples for HPV testing by immigrant women for insights into how future research using this emerging approach with unique subpopulations of women may improve rates of CCS compared to current standards of care. Although there have been other reviews that examined CCS among under-screened, never-screened, or otherwise "hard to reach" groups (Madzima et al, 2017;Marshall et al, 2019), we add to the literature by examining the methods and results from studies examining self-collection by immigrant women in order to guide future research design that will inform culturally tailored approaches to self-collection, and to consider the ways in which public health nurses can facilitate the use of this emerging strategy with these unique populations. Although we are aware that experiences vary widely and are dependent on numerous factors including immigration or citizenship status, we use the term immigrant broadly to refer to all foreign-born women residing in a country of resettlement.…”
mentioning
confidence: 99%